The diagnostic dilemma of a pregnant woman presenting with an isolated sixth nerve palsy: A case report. (December 2020) - Rengaraj, Nithya; Keepanasseril, Anish; Dorairajan, Gowri; Subbaiah, Murali; Nair, Pradeep P; Barathi, Deepak
Pregnant women presenting with isolated cranial palsies are uncommon. Isolated sixth nerve (abducens nerve) palsy can occur for a variety of reasons and neuroimaging is often performed to identify an underlying cause. We report a case of a woman in her third pregnancy with preeclampsia who presented with an isolated sixth nerve palsy. The diagnosis of aseptic cavernous sinus thrombosis was made and she subsequently made a full recovery.